An updated OECD framework on drivers of trust in public institutions to meet current and future challenges - Brezzi, Monica (OECD Working Papers on Public Governance, 2021)
Trust between citizens and their governments is crucial for the legitimacy and functioning of democracies. This paper discusses the main determinants of people's trust in public institutions and their measurement, in times of crisis as well as for a long-term, strong, inclusive and green recovery. It presents evidence on the great variation in the levels and drivers of trust across public institutions, across levels of government within countries, and among population groups. It also identifies three main trust challenges for public governance that were heightened by the COVID-19 crisis: i) people's views on the credibility and effectiveness of government action on intergenerational and often global challenges; ii) the changes in political participation and political attitudes; and iii) an increasing distrust of and disengagement from democratic processes. Building on previous OECD work, and taking into account lessons from other crises and handling of the COVID-19 pandemic, the paper introduces a revised and expanded version of the OECD Framework on Drivers of Trust in Public Institutions. Furthermore, it discusses how this Framework is applied in the OECD Trust Survey. Both the Framework and the Survey aim to provide governments with actionable evidence to build and maintain people's trust as the basis for successful planning and policy reforms, allowing democracies to be fitter, stronger and more resilient in the future